2020
DOI: 10.1080/13676261.2020.1820970
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to leave home during the transition to emerging adulthood among Turkish adolescents

Abstract: Although the age of leaving home has increased during the past few decades, senior year in high school remains a significant period during which many adolescents consider moving out, especially to attend university. However, the role of personal, practical and familial factors on adolescents' motivation to leave home prior to the actual transition are still unknown. The current study investigated adolescents' motivation to leave home while they still lived with their parents and its association with adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This group of adolescents also tended to move out earlier than their peers. Together, these findings are similar to other studies which shows that higher SES adolescents are more motivated to move out and tend to do so earlier than their lower SES peers ( 77 80 ). This higher motivation to live on one's own could reflect the greater decrease in depressed mood experienced afterwards.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This group of adolescents also tended to move out earlier than their peers. Together, these findings are similar to other studies which shows that higher SES adolescents are more motivated to move out and tend to do so earlier than their lower SES peers ( 77 80 ). This higher motivation to live on one's own could reflect the greater decrease in depressed mood experienced afterwards.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that this could be due to higher partner preferences (e.g., higher educational credentials and better income) among higher SES youth, but also parents expecting more thoughtful decisions in terms of partner choice ( 85 , 86 ). Another factor could be that a negative family climate and conflictual relationships with parents (both of which are common among lower SES) are motivating factors for moving in with a partner early on ( 77 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding home-leaving, research shows that what matters more for well-being is that emerging adults' living situations reflect their personal and autonomous motivation [27]. In high school, adolescents already differ in the extent to which they are motivated to leave home after they graduate [32]. However, some students may not have another option but to move out to attend university.…”
Section: Changes In Well-being During the Transition To University An...mentioning
confidence: 99%